Investment Liberalisation, Technology Take-off and Export Market Entry: Does Foreign Ownership Structure Matter? - Sourafel Girma; Yundan Gong; Holger Görg; Sandra Lancheros (Institute for the Study of Labor (IZA), 2015)
Before and after its accession to the WTO in 2001, China has undergone a far-reaching investment liberalisation. As part of this, existing restrictions on foreign ownership structure and mandatory export and technology transfer requirements imposed on foreign firms have been lifted in a number of industries. Against this background we identify the causal effects of foreign acquisitions on export market entry and technology take-off and evaluate whether the level of foreign ownership plays a role in stimulating these changes. Using doubly robust propensity score reweighted bivariate probit regressions to control for the selection bias associated with firm level foreign acquisition incidences, we uncover strong but heterogeneous positive effects on export activity for all types of foreign ownership structure. We also find that minority foreign owned acquisition targets experience higher likelihood of R&D, providing evidence that joint ventures can contribute positively to China's "science and technology take-off".
Keywords: F23; 330; investment liberalization; FDI; China; propensity score reweighting; doubly robust estimation